Perilaku Pencarian Informasi Guru di SMA Negeri 1 Pantai Cermin - Amalia, Syafika; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This study aims to find out how the information seeking behavior of teachers at SMA Negeri 1 Pantai Cermin. This study uses a quantitative descriptive method. The research instrument is a questionnaire. The instrument test uses validity and reliability tests. Data were analyzed using the mean to calculate the average value of each statement and calculate the grand mean to calculate the average of each indicator and variable. The results showed: (1) very high category initiation, high category exploration, high category monitoring, high category categorizing, high category sifting, high category resource selection, high category collection, and very high ending category. (2) the teachers of SMA Negeri 1 Pantai Cermin look for information using the internet rather than going to the library. (3) there are statements with low average scores on exploration, monitoring, categorizing, and collection.